2020
DOI: 10.1097/cm9.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Delayed graft function is correlated with graft loss in recipients of expanded-criteria rather than standard-criteria donor kidneys: a retrospective, multicenter, observation cohort study

Abstract: Background: Although the use of expanded-criteria donors (ECDs) alleviates the problem of organ shortage, it significantly increases the incidence of delayed graft function (DGF). DGF is a common complication after kidney transplantation; however, the effect of DGF on graft loss is uncertain based on the published literature. Hence, the aim of this study was to determine the relationship between DGF and allograft survival. Methods: We conducted a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
14
0
5
Order By: Relevance
“…The impact of DGF on graft survival is well established, as shown in a recently published large multicenter study ( 7 ). However, controversy is still out on whether the worst graft survival is restricted only to recipients of kidneys from standard criteria donors ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of DGF on graft survival is well established, as shown in a recently published large multicenter study ( 7 ). However, controversy is still out on whether the worst graft survival is restricted only to recipients of kidneys from standard criteria donors ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that recipients with DGF had a 41% increased risk of graft loss [ 20 ]. Our previous study also found that DGF is an independent risk factor for graft survival in recipients with ECD kidneys [ 21 ]. mtDNA levels have been confirmed as a predictive marker of AKI, and correlate with severity of renal dysfunction in chronic kidney injury [ 22 ].…”
Section: Discussionmentioning
confidence: 87%
“…DGF and GR are caused by complex factors with varying severities. However, both DGF and GR seem to be good predictors for long-term outcomes after kidney transplantation, especially deceased donors (25)(26)(27). Ischemia and reperfusion injury are complex pathophysiological phenomena, inevitable in kidney transplantation, and are major mechanisms for DGF after transplantation.…”
Section: Kidney Function In Kidney Transplant Patients With Positivementioning
confidence: 99%